2018
DOI: 10.1055/a-0637-1601
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound for Early Prediction of Response of Breast Cancer to Neoadjuvant Chemotherapy

Abstract: Some TIC parameters obtained by CEUS may allow prediction of the response of breast cancer to NAC at a very early time point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
(28 reference statements)
0
24
0
Order By: Relevance
“…Using TIC analyses, a (significant) decrease in wash-in/wash-out AUC 26 as well as an increase in RT 27 can be seen. Some TIC parameters obtained by CEUS may allow prediction of the response of breast cancer to NAC at a very early point of time 10 , 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Using TIC analyses, a (significant) decrease in wash-in/wash-out AUC 26 as well as an increase in RT 27 can be seen. Some TIC parameters obtained by CEUS may allow prediction of the response of breast cancer to NAC at a very early point of time 10 , 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…A change in dynamic contrast curves after neoadjuvant treatment has been shown to correspond to treatment response. 5 , 7 A reduction in PI, gradient, and increase in TTP indicates response due to the decrease in blood flow and reduction of blood vessel density in tumor tissue. If a lack of response can be identified early in the course of the treatment, an alternative treatment strategy can be implemented to benefit the patient.…”
Section: Discussionmentioning
confidence: 99%
“… 4 CEUS seems to be a promising method to monitor response during and after neoadjuvant treatment. 5 7 …”
Section: Introductionmentioning
confidence: 99%
“…52,53 TIC parameters were analyzed for different ROIs in Lee et al research. 54 ROI 1, ROI 2, ROI 3, and ROI 4 targeted the hotspot area of greatest enhancement, area of hyperenhancement, entire tumor on grayscale ultrasound and normal parenchyma, respectively, and the results led to a recommendation for the less subjective ROI 2 or ROI 3. Studies have confirmed that breast CEUS combined with TIC curve analysis not only provides information about blood perfusion but also provides a variety of quantitative parameters that greatly improve the accuracy of predicting the response to NAC.…”
Section: Contrast-enhanced Ultrasound (Ceus) For Assessing Response To Nacmentioning
confidence: 99%